2021
DOI: 10.2147/idr.s300754
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Chest Computed Tomography Findings: 1030 Cases of Drug-Sensitive Tuberculosis versus 516 Cases of Drug-Resistant Tuberculosis

Abstract: Purpose: To investigate the CT features of drug-resistant pulmonary tuberculosis (DR-PTB) and the diagnostic value of CT in DR-PTB diagnosis to provide imaging evidence for the timely detection of drug-resistant Mycobacterium tuberculosis. Materials and Methods: A total of 1546 cases of pulmonary tuberculosis (PTB) with complete clinical data, chest CT images and defined drug sensitivity testing results were consecutively enrolled; 516 cases of DR-PTB were included in the drug-resistant group, and 1030 cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 28 publications
1
22
2
Order By: Relevance
“…This finding can be supported by some previous study results. 23,[32][33][34] Additionally, our results showed that destroyed lung, bronchial stenosis, pleural and pericardial thickening were frequently observed in MDR-PTB, which were less commonly mentioned in the previous studies. The aforementioned CT features are closely associated with extensive fibrous tissue hyperplasia and bronchopulmonary structure destruction and are highly suggestive of a chronic TB course, which are consistent with some clinical features (eg, retreated history or longer previous anti-TB treatment) of patients with MDR-PTB presented herein.…”
Section: Discussionsupporting
confidence: 45%
“…This finding can be supported by some previous study results. 23,[32][33][34] Additionally, our results showed that destroyed lung, bronchial stenosis, pleural and pericardial thickening were frequently observed in MDR-PTB, which were less commonly mentioned in the previous studies. The aforementioned CT features are closely associated with extensive fibrous tissue hyperplasia and bronchopulmonary structure destruction and are highly suggestive of a chronic TB course, which are consistent with some clinical features (eg, retreated history or longer previous anti-TB treatment) of patients with MDR-PTB presented herein.…”
Section: Discussionsupporting
confidence: 45%
“…Another, small study [ 7 ], utilized data from 144 patients and found that the presence of multiple cavities is a good predictor for DR-TB. A much larger study [ 8 ], compared 516 DR-TB and 1030 DS-TB cases, obtaining an AUC of 0.83 using a regression model. This study observed that the co-existence of multiple findings (multiple cavities, thick-walled cavities, disseminated lesions along the bronchi, whole-lung involvement) was indicative of DR-TB.…”
Section: Previous Workmentioning
confidence: 99%
“…A logistic regression analysis has been carried out based on the differential representations on chest CT scans between DR‐TB and DS‐TB. Various characteristics, including wider lung involvement range, emphysema, bronchial dissemination, multiple cavities, exudative lesions, and so on, may participate in DR‐TB prediction 13 . Additionally, in specific DR‐TB subtypes, features of lesion range and cavities manifest discriminatively as well.…”
Section: Discussionmentioning
confidence: 99%
“…Besides laboratory tests, radiology plays a pivotal role in TB screening and diagnosis owing to its accessibility and efficiency 10 . Previous evidence has revealed that certain manifestations on chest computed tomography (CT) volumes, such as pulmonary nodules, thick‐wall cavities, consolidations, bronchiectasis, whole‐lung involvement, disseminated lesions, and so on, are more frequently observed in DR‐TB 11–13 . Additionally, cavities and lesion extent are characterized differently among patients with RR‐TB, multidrug‐resistant tuberculosis (MDR‐TB), and XDR‐TB, implying the diagnostic potential of chest CT imaging 14 …”
Section: Introductionmentioning
confidence: 99%